Database on the structure of small ribosomal subunit RNA. - Van de Peer, Y (1997)
The Antwerp database on small ribosomal subunit RNA now offers more than 6000 nucleotide sequences (August 1996). All these sequences are stored in the form of an alignment based on the adopted secondary structure model, which is corroborated by the observation of compensating substitutions in the alignment. Besides the primary and secondary structure information, literature references, accession numbers and detailed taxonomic information are also compiled. For ease of use, the complete database is made available to the scientific community via World Wide Web at URL http://rrna.uia.ac.be/ssu/ .